Numerical Investigation of a Methane Leakage from a Geothermal Well into a Shallow Aquifer. Issue 4 (8th November 2019) - D'Aniello, Andrea; Fabbricino, Massimiliano; Ducci, Daniela; Pianese, Domenico
Abstract : The potential environmental impacts on subsurface water resources induced by unconventional gas production are still under debate. Solving the controversy regarding the potential adverse effects of gas leakages on groundwater resources is therefore crucial. In this work, an interesting real‐world case is presented in order to give further insight into methane multiphase and transport behavior in the shallow subsurface, often disregarded compared to the behavior in the deep subsurface. Multiphase flow and solute transport simulations were performed to assess the vulnerability of an existing shallow unconfined aquifer with respect to a hypothetical methane leakage resulting from a well integrity failure of a former deep geothermal well. The analysis showed that migration of gaseous methane through the aquifer under examination can be extremely fast (of the order of a few minutes), occurring predominantly vertically upwards, close to the well. By contrast, dissolved methane migration is largely affected by the groundwater flow field and occurs over larger time scales (of the order of months/years), covering a greater distance from the well. Overall, the real concern for this site in case of gas leakages is the risk of explosion in the close vicinity of the well. Predicted maximum gaseous fluxes (0.89 to 22.60 m 3 /d) are comparable to those reported for leaking wells, and maximum dissolved methane concentrations may overcome risk mitigation thresholds (7 to 10 mg/L) in a few years. Therefore, surface and subsurface monitoring before decommissioning is strongly advised to ensure the safety of the site. Abstract : Article impact statement : Gas leakages impact groundwater quality. Multiphase and solute transport modeling is used to analyze gas migration in a real aquifer.